2019
DOI: 10.1029/2019gl082599
|View full text |Cite
|
Sign up to set email alerts
|

Increased Extreme Coastal Water Levels Due to the Combined Action of Storm Surges and Wind Waves

Abstract: The dependence between extreme storm surges and wind waves is assessed statistically along the global coasts using the outputs of two numerical models consistently forced with the same atmospheric fields. We show that 55% of the world coastlines face compound storm surge wave extremes. Hence, for a given level of probability, neglecting these dependencies leads to underestimating extreme coastal water levels. Dependencies are dominant in midlatitudes and are likely underestimated in the tropics due to limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 51 publications
(70 reference statements)
4
80
0
Order By: Relevance
“…Then, correlation is assessed with the Kendall rank correlation. Previous studies in the US coast and globally have suggested that an indicative value of 0.2 may be already significant enough (Wahl and Chambers, 2014) to require the computation of the joint probability using a multivariate approach such as the Copula functions (e.g., Sayol and Marcos, 2018;Enríquez et al, 2019;Marcos et al, 2019). Correlations for those independent events are shown in Figure 4C for all percentiles being in all cases very low with FIGURE 5 | Schematic representation of the approach followed in the study.…”
Section: Correlation Between Skew-surges and H Smentioning
confidence: 99%
“…Then, correlation is assessed with the Kendall rank correlation. Previous studies in the US coast and globally have suggested that an indicative value of 0.2 may be already significant enough (Wahl and Chambers, 2014) to require the computation of the joint probability using a multivariate approach such as the Copula functions (e.g., Sayol and Marcos, 2018;Enríquez et al, 2019;Marcos et al, 2019). Correlations for those independent events are shown in Figure 4C for all percentiles being in all cases very low with FIGURE 5 | Schematic representation of the approach followed in the study.…”
Section: Correlation Between Skew-surges and H Smentioning
confidence: 99%
“…The majority of these studies have been undertaken on a small spatial scale for specific localised regions, e.g. Fuzhou, China (Lian et al, 2013); Tsengwen River basin, Taiwan (Chen and Liu, 2014); Hudson River, USA (Orton et al, 2015); Shoalhaven River, Australia (Kumbier et al, 2018); the Rhine delta, Netherlands (Kew et al, 2013 andKhanal et al, 2018); Brest, France (Mazas and Hamm, 2017); Santander, Spain (Rueda et al, 2016); Ravenna, Italy (Bevacqua et al, 2017); and the river Trent, the Yare basin, the river Ancholme, and the rivers Taff and Lewes in East Sussex in the UK (Granger, 1959;Mantz and Wakeling, 1979;Thompson and Law, 1983;Samuels and Burt, 2002;and White, 2007, respectively). These studies have typically examined the dependence between two source variables only, such as storm surge (or storm tide) and river discharge, between storm surge and waves, or between storm surge and rainfall (as a proxy for run-off).…”
Section: Introductionmentioning
confidence: 99%
“…Each process is forced by different environmental processes (oceanographic, meteorological, and hydrological) acting at varying spatial (local to global) and temporal scales (hours to centuries; Leonard et al, ). Extreme water levels on beaches are underestimated without considering wave run‐up and setup (e.g., Marcos et al, ), yet wave climates can include both local and distant swell components generated by faraway storms on the order of weeks prior to arrival (Hegermiller et al, ). Similarly, nontidal residuals are a product of regional wind stresses and barometric pressure anomalies occurring in the weather‐band timescale, as well as regional processes such as seasonally varying upwelling and downwelling, and large‐scale climate phenomena affecting basin‐wide circulations (i.e., El Niño Southern Oscillation [ENSO] and Pacific Decadal Oscillation; Merrifield et al, ).…”
Section: Introductionmentioning
confidence: 99%